The contemporary organizations type mp3 and their cultural influence (2011)
The article reflects on the cultural influence of contemporary organizations with des-hierarchical structures and not sequential internal processes, which Professor Richard Sennett has called MP3 organizations. From the organizational structures described by Alvaro Zapata, the distinction between labour and work of Hannah Arendt, Foucault´s monitoringmechanisms and contextualization in Colombia, discusses the low institutional loyalty, the ecrease in informal trust between workers and weakening of institutional knowledge.